USAGE OF ANTISEPTICS AND HAEMOSTATIC AGENTS AT ONE-VISIT EXTIRPATION TREATMENT METHOD OF PULPITIS - Nikolishin, A.K.; Geranin, S.I. (World of Medicine and Biology, 2010)
Article describes literature review of microflora meaning in etiology and pathogenesis of pulpitis, it’s quantitative and quality composition, as well as influence of haemostatic agents and antiseptics on results of one-visit extirpation treatment method of irreversible pulpitis.